Nearpod Media for the Development of Teaching Materials for the Production Écrite Débutante Course - Rabiah Adawi; Zulherman (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This research aims to: (1) develop teaching materials for the Production Écrite Débutante course usingmedianearpodto improve the writing skills of students in the French Education Study Program, (2) assess the suitability of the teaching materials for the Production Écrite Débutante course usingmedianearpod.This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research instruments used were questionnaires and written tests. This research is limited to research on the development of teaching materials for the Production Écrite Débutante course using nearpod learning media on teaching materials for possessive pronouns in French to improve the writing skills of UNIMED French Language Education Study Program students. The output targets of this research are publication of international journal articles with a reputation in Scopus/WoS/Copernicus, final research reports registered with copyright, textbooks with ISBN, speakers at international scientific meetings, publications in international proceedings indexed by Scopus or Web of Science.